Photocatalytic degradation of Congo Red by zinc sulfide quantum dots produced by anaerobic granular sludge - Jacob, Jaya Mary (Environmental technology, 2022)
ABSTRACTSulfate reducing bacteria present in anaerobic granular sludge mediate the metabolic conversion of sulfate to sulfide. In the presence of heavy metals, sulfides precipitate as metal sulfides. In this study, dissimilatory sulfate reduction was coupled to the precipitation of zinc as ZnS quantum dots (QDs) at ambient conditions. The biogenic ZnS QDs had average sizes of 5-7 nm and were formed within 2-4 days of incubation. X-ray diffraction analysis indicated that the biosynthesised ZnS QDs possessed a crystalline cubic lattice structure. The organics present during ZnS biosynthesis were characterized using 3D-fluorescence excitation-emission measurements (FEEM) and the presence of an organic coating on the biogenic ZnS QDs was affirmed using FTIR analysis. The UV-visible absorption spectra of the samples exhibited a prominent absorption peak below 325 nm, which is the characteristic of the surface plasmon resonance of ZnS QDs. The band gap energy of the biogenic ZnS QDs was estimated to be 3.84 eV, comparable to the values reported for chemically synthesised ZnS QDs. The direct band gap energy indicates a large redox potential and carrier mobility, which capacitate the application of these QDs as effective photocatalysts for the photo-assisted decolourization of dyes, as illustrated for the dye congo red